Context dependency of conditioned aversions to familiar and novel fluids - Ishii, Kiyoshi; Iguchi, Yoshio; Sawa, Kosuke (Learning and motivation, 2006)
Using a context discrimination procedure and rats as the subjects, the formation of context-dependent aversions to novel and familiar fluids was investigated. Experiment 1 revealed that context dependency could be established to a novel fluid (saccharin) after three cycles of context discrimination training and that the acquired context dependency was revealed also to a second familiar fluid (water) presented in the following test. Experiment 2 showed that the formation of the context-dependent aversion and its transfer to a second fluid was not affected by whether fluid presented during discrimination was novel (saccharin) or familiar (water). Experiment 3 demonstrated that when the same water was given both in the two training contexts and in the home cages of the subjects during discrimination, the context-dependent aversion formed was specific to it. These findings can be explained in terms of a simple summation effect of fluid-nausea and context-nausea associations.